STRATEGIC ROLE OF DIGITAL MARKETING AND SERVICE QUALITY IN SHAPING CONSUMER PURCHASE DECISIONS: EVIDENCE FROM MSMES IN BANDA ACEH - Fandi Bachtiar (GREET, 2026)
This study aims to analyze the strategic role of digital marketing and service quality in shaping consumer purchase decisions among Micro, Small, and Medium Enterprises (MSMEs) in Banda Aceh. In the era of rapid technological advancement and increasing market competition, MSMEs are required to adopt effective marketing strategies and maintain excellent service quality to attract and retain customers. This research employs a quantitative approach using a survey method. Data were collected from 150 consumers who had purchased products from MSMEs in Banda Aceh through structured questionnaires. The collected data were analyzed using multiple linear regression with the assistance of SPSS software. The findings indicate that digital marketing has a positive and significant effect on consumer purchase decisions. Likewise, service quality also shows a positive and significant influence on purchase decisions. Simultaneously, both variables contribute substantially to explaining variations in consumer purchasing behavior. These results suggest that MSMEs should strengthen their digital presence through social media, online promotions, and interactive communication while continuously improving service responsiveness, reliability, and customer satisfaction. The study provides practical implications for MSME owners and policymakers in developing competitive business strategies to enhance local economic growth.